ELECTRONIC-BASED SERVICES AS AN EFFORT TO PREVENT PUBLIC SECTOR GRATIFICATION IN MEDAN CITY - Az-Zahra, Amalia amal; Nasution, Rasina Padeni (Lex Lectio Law Journal, 2024)
AbstractThe public essentially agrees to condemn acts of corruption, but the public actually justifies the behavior of paying thanks under the guise of gratification. Even though an online service system has been implemented through the SIBISA application, it does not rule out the possibility that gratuitous behavior still exists. This research aims to describe the implementation of the SIBISA application in DISDUKCAPIL Medan City. The author also analyzes the service system through SIBISA in an effort to prevent gratification in the public sector. This research is empirical juridical research, namely legal research regarding the enactment or implemen tation of normative legal provisions in action at each specific legal event that occurs in society. with a field research approach, namely research whose object is about symptoms or events that occur in community groups. The results of SIBISA implementation can be said to be very relevant in efforts to eradicate corruption because information on procedures for managing population documents is displayed at the entrance to the DISDUKCAPIL office so that people do not need to use CALO.AbstrakMasyarakat pada hakikatnya sepakat untuk mengecam tindakan korupsi, namun masyarakat justru membenarkan perilaku mengucap syukur berkedok gratifikasi. Meski sudah diterapkan sistem pelayanan online melalui aplikasi SIBISA, namun tidak menutup kemungkinan masih ada perilaku gratifikasi. Penelitian ini bertujuan untuk mendeskripsikan implementasi aplikasi SIBISA di DISDUKCAPIL Kota Medan. Penulis juga menganalisis sistem pelayanan melalui SIBISA dalam upaya pencegahan gratifikasi di sektor publik. Penelitian ini merupakan penelitian yuridis empiris, yaitu penelitian hukum mengenai pemberlakuan atau pelaksanaan ketentuan hukum normatif dalam tindakan pada setiap peristiwa hukum tertentu yang terjadi dalam masyarakat. dengan pendekatan penelitian lapangan yaitu penelitian yang objeknya mengenai gejala atau peristiwa yang terjadi pada kelompok masyarakat. Hasil penerapan SIBISA dapat dikatakan sangat relevan dalam upaya pemberantasan korupsi karena informasi tata cara pengurusan dokumen kependudukan dipajang di pintu masuk kantor DISDUKCAPIL sehingga masyarakat tidak perlu menggunakan CALO.